A Cadaveric Load Analysis of the Supramalleolar Osteotomy In The Setting of an Osteochondral Pseudolesion: Quantifying Chondral Off-loading. Issue 4 (16th October 2019) - Tracey, Joseph; Glisson, Richard; Verschae, Gregorio; Wagner, Emilio; Gross, Christopher; Easley, Mark
Category: Ankle, Ankle Arthritis Introduction/Purpose: The supramalleolar osteotomy (SMO) serves as a means to alter joint load transmission and shield damaged areas of cartilage within the tibiotalar joint. The aim of this study was to directly measure the changes in pressure attributed to varying degrees of SMOs (varus and valgus); with and without an osteochondral (OCD) pseudolesion, and in multiple ankle alignments (Dorsiflexion, neutral, and plantarflexion). We hypothesize measurement metrics to be reduced with increasing degrees of SMO. Methods: 6 cadaver specimens were in included in the biomechanical study (sectioned at the mid-tibia). A pressure sensor was used to measure load, load area, and peak pressure within the tibiotalar joint. SMOs of 3, 6, 9, and 12 degrees in varus or valgus were performed. A servohydraulic machine was used to transmit 400 and 800 N through the specimens; in 10 degrees of dorsiflexion, neutral, or in 10 degrees of plantarflexion during load transmission. Measurements were performed in undisturbed joints, followed by re-measurement in the presence of a created 9 mm diameter pseudolesion. Results: Load was not changed (only significant changes reported) in the presence of a lesion. For the load, it was more influenceable at 800 N, changes were observed in higher degree SMOs, and changes were only observed in neutral and dorsiflexion. Changes in area were only observed when 12 degrees of varus or valgus SMOs were used. Peak Pressure was the only modifiable metric in the presence of a pseudo-lesion, reductions were more common at 800 N, and in the absence of a pseudolesion there was an incremental reduction in medial peak pressure when increasing varus SMOs were performed (dorsiflexion). Conclusion: Medial peak pressure tended to decrease with varus SMOs in neutral and dorsiflexion. Medial load tended to decrease with varus osteotomies in 10 degrees of dorsiflexion. A 12 degree varus SMO was the only SMO to influence a pseudolesion.